2009
DOI: 10.1039/b905298d
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for C-6 modification of guanine nucleosides

Abstract: A facile method for the introduction of various substituents at the C-6 position of guanosine and 2′-deoxyguanosine is reported. In a simple, 1-step transformation, tert-butyldimethylsilyl protected guanosine and 2′-deoxyguanosine were converted to the O 6 -(benzotriazol-1-yl) derivatives via reaction with 1H-benzotriazol-1-yloxy-tris(dimethylamino)phosphonium hexafluorophosphate (BOP) and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). The easily isolated, stable and storable, O 6 -(benzotriazol-1-yl) guanosine der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 24 publications
1
55
1
Order By: Relevance
“…Some authors use firm-level, rather than BOP-initiative-level, measures to assess profitability. Lakshman (2009), for instance, cites a 30% increase in market capitalization for ITC Ltd as its focus on BOP markets grows.…”
Section: Outcomes Of Bop Initiativesmentioning
confidence: 99%
“…Some authors use firm-level, rather than BOP-initiative-level, measures to assess profitability. Lakshman (2009), for instance, cites a 30% increase in market capitalization for ITC Ltd as its focus on BOP markets grows.…”
Section: Outcomes Of Bop Initiativesmentioning
confidence: 99%
“…Syntheses of compounds 1 , 4 , 7 , and 8 have been published previously, 11,15 and compounds 9 – 14 were synthesized via analogous procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Conversion of O 6 -(benzotriazol-1-yl)guanosine derivative 7 to the O 6 -allyl compound 15 was accomplished as described. 15 Diazotization-bromination then gave the 2-bromo- O 6 -allyl guanosine derivative 16 . 25 Notably, when this reaction was conducted in CH 2 Cl 2 a minor byproduct ( 17 ) was observed that was consistent with the allyl group dibromination, on the basis of 1 H NMR and HRMS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The authors were surprised to find that electron transfer was more efficient in duplexes containing a mismatch, possibly because the mismatch site enables electron injection or hopping beyond this site. Synthetic methods of relevance to DNA and RNA chemistry continue to be developed (Lakshman & Frank, 2009, Kaloudis et al, 2009, Edwards et al, 2009& Ohkubo et al, 2009). The chemical biology of DNA quadruplexes continues to develop.…”
Section: The Chemical Biology Of Nucleic Acidsmentioning
confidence: 99%